Isotopic niches of Mesopelagic fish on the southern Kerguelen Axis: variation and overlap - Woods, B; Walters, A; Hindell, M; Trebilco, R (Australian Antarctic Division, 2019)
Mesopelagic fish are an important but poorly understood mid-trophic component of Southern Ocean food webs. This study aimed to investigate the trophic role of mesopelagic fish in the southern Kerguelen Plateau region. We used carbon and nitrogen stable isotopes to quantify the isotopic niches of key mesopelagic fish species (six from the family Myctophidae, and one from Bathylagidae), to investigate variation along the δ 15 N and δ 13 C axes between species, and to examine the relationship between fish body length and δ 15 N within species and across the community. The assemblage of key mesopelagic fish occupied similar isotopic niche space with overlap among species in both δ 13 C and δ 15 N values. However, there were areas of non-overlapping isotopic niche space between species providing evidence of niche partitioning most likely driven by interspecific differences in diet and body size. At the community level, fish standard length was positively correlated with δ 15 N suggesting size-related differences in diet between species. However, within-species relationships between fish standard length and δ 15 N were weak. Overall, the findings from this study suggest that while there is a degree of trophic diversity among the taxa examined, this assemblage comprises a single energy pathway, which is informative for overall understanding of food-web architecture as well as development of trophically orientated ecosystem model for this region.